Oxidative stress, apoptosis and abnormal expression of apoptotic protein and gene and cell cycle arrest in the cecal tonsil of broilers induces by dietary methionine deficiency. (December 2018) - Wu, B.Y.; Zhu, M.; Ruan, T.; Li, L.J.; Lyu, Y.N.; Wang, H.S.
Abstract: Methionine (Met) is often called the first limiting amino acid in birds. Broilers have high requirement for Met, so they are at high risk of Met deficiency. The aims of the present research is to study the effects of Met deficiency on the histomorphological changes, antioxidant functions, apoptosis and cell cycle in the cecum tonsil of broilers. A batch of 120 one-day-old Cobb broilers in total are divided into two groups and fed on a Met deficiency diet or a control diet for six weeks, followed by analysis using the methods of experimental pathology, biochemical method, immunohistochemical method, ELISA, FCM, Tunel assay, and qRT-PCR. Results showed that the cecal tonsils were impaired, and the SOD, CAT and GSH-Px activity, the ability to suppression on the hydroxy radicals, and the content of GSH reduced in Met deficiency group comparing to the control group. In contrast, the MDA content is higher in Met deficiency group. As measured by immunohistochemical method, ELISA, Tunel, FCM and qRT-PCR, increased proportion of apoptotic cells, abnormal content or expression of apoptotic proteins, as well as cell cycle arrest were observed. In conclusion, dietary Met deficiency imposes a severe impact on the cecal tonsils, mainly in the forms of histological injury, cell cycle arrest, oxidative stress, and increased cellular apoptosis. The oxidative stress leads to cellular apoptosis and then induces the injury of the cecum tonsils. The local intestinal mucosal immune system would finally be injured by the oxidative stress and apoptosis in the intestine. Highlights: No studies on effect of Met on apoptosis and cell cycle of the cecal tonsil. Met deficiency-induced cecal tonsil oxidative stress. qRT-PCR, FCM, Immunohistochemistry, TUNEL and ELISA methods are used in this study. Met deficiency impose a severe impact on the cecal tonsil.